Review of Automated Code Refactoring of C# Programs - Derezinska, Anna; Sygocki, Dawid (2023 18th Conference on Computer Science and Intelligence Systems (FedCSIS), 2023)
Code refactoring is supported by many Integrated Development Environments. This paper is focused on the automated code refactoring of C# programs. We have analyzed more than sixty refactorings available in three popular IDEs. We cataloged different restrictions, defects, and other quality concerns associated with the implementation of the refactorings, taking into account both modification of the production code and of the corresponding test cases. An extension to automate selected refactoring improvements has been developed for the ReSharper platform and experimentally verified.